Conventional and transgenic herbicide‐resistant soybean cultivars yielded similarly across five site‐years in Nebraska. Issue 2 (2nd September 2022) - Mobli, Ahmadreza; Arneson, Nicholas J.; Spicka, Steve; Glewen, Keith; Proctor, Christopher A.; Werle, Rodrigo
Abstract: Soybean [ Glycine max (L.) Moench.] yield is determined by interactions amongst soybean cultivars' genetic potential, agronomic practices, and environmental conditions. Despite the high adoption of herbicide‐resistant soybean cultivars across Nebraska and the United States, the comparative yield potential of non‐herbicide‐resistant ("conventional") cultivars in not well understood. A field experiment was conducted at five locations across Nebraska in 2017 and 2018 to determine the effect of row spacing (15 and 30 in), cultivar maturity group (2.2–2.4 and 3.2), and herbicide resistance traits (conventional, glyphosate‐resistant, and glyphosate‐ and dicamba‐resistant) on soybean yield. Narrow row spacing increased the soybean yield in three of five research locations. The soybean yield in Auburn in 2017, Albion in 2018, and Cedar Bluffs in 2018 increased by 11.9, 10.2, and 11.4% in narrow compared with wide rows, respectively. Cultivar maturity group and herbicide resistance traits did not affect soybean yield under weed‐free experimental conditions. These results suggest that growers could benefit from earlier maturity groups, as they provide an opportunity for earlier harvest, allowing growers to better spread their field activities in the fall. The grain yield potential was similar between conventional and transgenic herbicide‐resistant cultivars. Therefore, conventional soybean cultivars can be a viable option when adequate weed management can be achieved through conventional weed management strategies. Core Ideas: Soybean yield was higher in narrow row spacing than in wide rows in three of five locations. Early soybean maturity group cultivars (2.2‐2.4) yielded similarly to late (3.2) cultivars. Conventional cultivars had similar yield to transgenic herbicide‐resistant cultivars.